2014
DOI: 10.1002/ams2.68
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of lethal acetylsalicylic acid poisoning without hemodialysis

Abstract: Case: A woman aged in her 20s ingested approximately 99 g acetylsalicylic acid, and was transported to our hospital 2 h later. She was lucid, but complained of hearing loss and tinnitus. We performed gastric lavage and gave her activated charcoal several times. We attempted to maintain the urinary pH at 7.5 and output above 100 mL/h while preparing for urgent hemodialysis.Outcome: It was revealed after discharge that the blood concentration of acetylsalicylic acid was 103.8 mg/dL on admission (lethal dose leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…This beneficial effect of increasing urine pH was also reported by Morgan et al [137] when indirectly comparing two sets of patients with moderate and extreme urinary pH of 6.60 [6.00-7.05] and 7.88 [7.60-8.00], respectively. Several case reports have also demonstrated the value of urine alkalinization [138][139][140]. Thus, despite their poor quality, several studies have confirmed the enhanced urinary elimination of salicylates induced by urine alkalization.…”
Section: Recommendation In the Form Of An Expert Opinion/strong Consementioning
confidence: 99%
See 1 more Smart Citation
“…This beneficial effect of increasing urine pH was also reported by Morgan et al [137] when indirectly comparing two sets of patients with moderate and extreme urinary pH of 6.60 [6.00-7.05] and 7.88 [7.60-8.00], respectively. Several case reports have also demonstrated the value of urine alkalinization [138][139][140]. Thus, despite their poor quality, several studies have confirmed the enhanced urinary elimination of salicylates induced by urine alkalization.…”
Section: Recommendation In the Form Of An Expert Opinion/strong Consementioning
confidence: 99%
“…Thus, despite their poor quality, several studies have confirmed the enhanced urinary elimination of salicylates induced by urine alkalization. These results have been repeatedly considered to be sufficient to recommend urine alkalization as an adequate first-line treatment for salicylate poisoning, avoiding the need for haemodialysis [133,[140][141][142].…”
Section: Recommendation In the Form Of An Expert Opinion/strong Consementioning
confidence: 99%